ANALISIS KESULITAN MENENTUKAN IDE POKOK PARAGRAF SISWA KELAS V SD NEGERI 45 KOTA TERNATE - Anggun Mansur; Kodrat Hi Karim; Darmawati Hady (PEDAGOGIK, 2023)
This research was conducted with the aim of (1) describing the ability of fifth grade students at SD Negeri 45 Kota Ternate in determining the main ideas of paragraphs, (2) knowing the factors that cause difficulties for grade V students at SD Negeri 45 Ternate City in determining the main ideas of paragraphs. This study used qualitative research methods. The collection of data used in this study are observation, tests, and interviews. The sample used in this study were 36 students.The results showed that: 1) out of 36 students who took the test, 17 students easily determined the main idea of a paragraph, while 19 students had difficulty determining the main idea of a paragraph including: 5 students (14%) had difficulty in understanding reading, 8 students (22%) had difficulty sorting out deductive and inductive paragraphs, and 6 students (17%) had difficulty distinguishing between deductive and inductive paragraphs. Based on the results of tests and interviews, there are 2 factors that cause students to experience difficulties, namely: the first is internal which includes, 1) students do not understand what is meant by the main idea; 2) students have not been able to sort out between main sentences and developer sentences; 3) students don't like the main idea material, 4) students' lack of interest in reading. The two external factors include: 1) the use of limited learning media causing students to feel bored during the learning process; 2) the lack of learning approaches carried out by parents of students at home; 3) less than optimal class management.